PENGARUH PERPUTARAN MODAL KERJA, LEVERAGE DAN LIKUIDITAS TERHADAP PROFITABILITAS SUB-SEKTOR ASURANSI DI BURSA EFEK INDONESIA - Musri Yulianti; Maria Karolina Deran Tupen (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to determine the effect of working capital turnover, leverage, and liquidity on profitability in the insurance sub-sector listed on the Indonesia Stock Exchange. This study uses secondary data in the form of monthly financial reports from 2018 to 2022. The results indicate that partially, working capital turnover has no significant effect on profitability, leverage has a significant effect on profitability, and liquidity has no significant effect on profitability. Simultaneously, working capital turnover, leverage, and liquidity influence profitability in insurance sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2022.